Body composition and selected anthropometric traits of elite Polish female judokas in relation to the performance of right-dominant, left-dominant, or symmetrical judo techniques in vertical posture (tachi waza) - Socha, M.; Witkowski, K.; Jonak, W.; Sobiech, K. A. (Archives of Budo, 2016)
Background and Study Aim: Judo is a sport with a complex structure of short and "intense movements". A judo competitor must possess high levels of strength, agility, and technical and endurance skills. The study aim is the relationship the body composition, the degree of symmetrization of muscle mass of the limbs, skinfolds and hand grip strength with respect to the preferred side of attacks in vertical posture (tachi waza) during judo matches.